2019
DOI: 10.1159/000501686
|View full text |Cite
|
Sign up to set email alerts
|

miR-29b Reverses T helper 1 cells/T helper 2 cells Imbalance and Alleviates Airway Eosinophils Recruitment in OVA-Induced Murine Asthma by Targeting Inducible Co-Stimulator

Abstract: Asthma is a complex chronic disease and the pathogenesis is still not entirely clear. In this study, we aimed to clarify the role and mechanism of miR-29b in the development of asthma. We observed that miR-29b levels were decreased in the lung and spleen of OVA-induced asthmatic mice. Reverse transcription-quantitative polymerase chain reaction and flow cytometry demonstrated that the inducible co-stimulator (ICOS) expression at mRNA and protein levels was elevated in the lung of asthmatic mice, and miR-29b ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…One of these miRNAs is miR-29b, which is involved in the development of asthma. This miRNA indirectly affects to Th2 response by regulating T-box transcription factors and IFN-γ production in T helper cells ( 181 ), so a lower expression of this miRNA in asthmatic lung allows a higher production of IFN-γ in order to recover Th1/Th2 balance in asthmatic lungs ( 182 ). According to miR-19a, Simpson et al.…”
Section: Mirnas In Lung Diseasesmentioning
confidence: 99%
“…One of these miRNAs is miR-29b, which is involved in the development of asthma. This miRNA indirectly affects to Th2 response by regulating T-box transcription factors and IFN-γ production in T helper cells ( 181 ), so a lower expression of this miRNA in asthmatic lung allows a higher production of IFN-γ in order to recover Th1/Th2 balance in asthmatic lungs ( 182 ). According to miR-19a, Simpson et al.…”
Section: Mirnas In Lung Diseasesmentioning
confidence: 99%
“…The experimental groups were designed as follows:‐ sham induction by the sterile PBS control group, asthma model group with OVA (Sigma‐Aldrich, St. Louis, MO, USA) induction and asthma model with PepN treatment group. For OVA‐induced allergic asthma, mice were intraperitoneally sensitized with 100 μg OVA suspended in 1 mg of aluminium hydroxide (Thermo Scientific, Waltham, MA, USA) in 200 μl of sterile PBS on days 0 and 7, followed by eight aerosol challenges with 5% (w/v) OVA in PBS for 30 min per day from day 14 to 21 (Yan et al, 2019). The control group mice were treated in the same way with PBS at the same time points.…”
Section: Methodsmentioning
confidence: 99%
“…in the present study, four differentially expressed circrnas were validated by qPCR, of which two were significantly upregulated and two were significantly downregulated. The regulatory network of circrna and mirna indicated that two of these upregulated circrnas (circ_0000455 and circ_0000629) could target mir-29b and mir-15a, respectively, which were previously reported to be negatively correlated with the occurrence of allergic reactions (41,42). The expression levels of inducible co-stimulator, a target gene of mir-29b, were also previously shown to be elevated in the lungs of asthmatic mice, and promoted Th2 cytokine production and eosinophilic inflammation (43).…”
Section: Discussionmentioning
confidence: 90%